Projecting of images in social communicative practice - Udris, Natalia (Visnyk of V. N. Karazin Kharkiv National University. Series Sociological studies of contemporary society: methodology, theory, methods, 2019)
The paper considers image as a leading factor of communicative practices and socio-cultural reality. The author’s definition of social communication as an exchange of synthetic communicative images is given. The process of creation of images in communicative practice is investigated. The definition of communicative image is formulated and its characteristics are described. The features of presentational and representational images are analyzed.